River bio-engineering solution for protecting banks and rehabilitating stream function; models for Bishnumati River, Kathmandu - Tamrakar, Naresh Kazi (Bulletin of the Department of Geology, 2010)
DOI: 10.3126/bdg.v13i0.3962Bulletin of the Department of Geology Vol.13 2010, pp.13-22